Compression and buckling after impact response of resin-infused thermoplastic and thermoset 3D woven composites. (15th February 2021) - Shah, S.Z.H.; Megat-Yusoff, P.S.M.; Karuppanan, S.; Choudhry, R.S.; Ud Din, Israr; Othman, A.R.; Sharp, K.; Gerard, P.
Abstract: Damage tolerance of a unique resin-infused thermoplastic (Elium) 3D fibre-reinforced composite (3D-FRC) is compared with the conventional resin-infused thermoset (Epoxy) 3D-FRC using compression after impact (CAI) tests and finite element simulations. Higher damage tolerance is demonstrated for the thermoplastic 3D-FRC as its CAI failure strength and CAI stiffness is nearly insensitive to the impact energy levels and subsequent damage, while in contrast, both these properties for the thermoset 3D-FRC get compromised significantly. The buckling performance shows a gradual, almost linear, reduction in critical buckling (44.5% reduction in 0–100 J) for the thermoplastic 3D-FRC. In comparison, the thermoset 3D-FRC shows a much steeper drop in critical buckling, which becomes more pronounced for the higher impact energy cases (84.5% reduction in 0–100 J). It is postulated that the local plastic deformation of the thermoplastic matrix at the impact site as well as better interfacial adhesion is responsible for its better damage tolerance.